Profissionais de saúde mental: olhares sobre internação compulsória de pessoas que usam crack - Andreeti, Tainara Oliveira (2019)
This Master's Dissertation aimed to reflect and problematize the practices of compulsory hospitalization of people who use crack, based on the experiences of health professionals from a Regional Conducting Group of the Psychosocial Care Network of the 4th Regional Health Coordination, observing how certain knowledges and practices mobilize affections and produce forms of work. It was intended to an approximation of the object "compulsory hospitalization by drugs, especially crack" in order to know the health-disease-care processes related to consumption and hospitalization, by the look of the professionals who participate in the order process of compulsory admissions of people who use crack. The project was within the scope of the Theory of Social Representations in its psychosocial approach and some studies that take into account not only the biophysiological body but the affections and knowledge produced through a group of health professionals. This was a participatory research study, with an ambience in the 4th Regional Health Coordination, located in Santa Maria, Rio Grande do Sul, Brazil, involving a documentary survey of the group meetings, observations of conductive mental health groups and notes in field diary. The first chapter, entitled "Theory of Social Representations and some concepts", had as proposal to present the main theory that bases this research. Following in the next chapter, we present an experience report whose aim was to report the implementation process of a group of the Psychosocial Care Network (RAPS), the 4th Regional Coordination of Health (CRS). Finally, the chapter entitled "Compulsory hospitalization from the perspective of mental health professionals” in which we aimed to understand, reflect and problematize the practice of Compulsory Hospitalization (CH), from the perspective of the mental health professionals that integrate the Regional Group of the Psychosocial Care Network (RAPS) of the 4th Regional Health Coordination (4th CRS). The results showed that the RAPS’ Regional Group becomes an important working tool for the SUS, as a space for discussion and articulation, in relation to the incentive to Permanent Education, to the promotion of humanized and integralized health care practices. It is noticed that the speech about compulsory hospitalization is usually validated by the biologist’s, medical/psychiatrics’ perspective on drugs, without questioning the real criteria for such a process. These thoughts and affections produce a practice of care that is crossed by the lack of of dialogues between the services and the Judiciary. Thus, the importance of new researches and practices of Permanent Education with the group is thought to follow up the problematizations, already in progress, regarding the proposals of care in mental health.